Neuromodulatory potential of phenylpropanoids; para-methoxycinnamic acid and ethyl-p-methoxycinnamate on aluminum-induced memory deficit in rats. (13th June 2019) - Rijal, Samita; Changdar, Nilanjan; Kinra, Manas; Kumar, Ayush; Nampoothiri, Madhavan; Arora, Devinder; Shenoy, Rekha R.; Ranganath Pai, K. Sreedhara; Joseph, Alex; Mudgal, Jayesh
Abstract: Para-methoxycinnamic acid (PMCA) and Ethyl-p-methoxycinnamate (EPMC) are reported to possess neuroprotective effect in reversing an acute memory deficit. However, there is a dearth of evidence for their therapeutic effect in chronic memory deficit. Thus, there is a scope to study these derivatives against the chronic model of cognitive dysfunction. The present study was aimed to determine the cognitive enhancing activity of PMCA and EPMC in aluminum-induced chronic dementia. Cognitive enhancing property of PMCA and EPMC was assessed using Morris water maze by analyzing spatial memory parameters such as escape latency, D-quadrant latency, and island entries. To find a possible mechanism, the effect of test compounds on altered acetylcholinesterase (AChE) activity and oxidative stress was determined in the hippocampus and frontal cortex of rats. Docking interaction of these derivatives with acetylcholinesterase enzyme and glutamate receptors was also studied. Treatment with PMCA and EPMC showed a significant improvement in spatial memory markers and altered hippocampal AChE activity in rats with cognitive dysfunction. The implication of hippocampal and cortical oxidative stress in memory impairment was confirmed with decreased catalase/increased thiobarbituric acid reactive substances (TBARS) in rats. PMCA and EPMC reversed the oxidative stress in the brain by negatively affecting TBARS levels. Against depleted catalase levels, PMCA was more effective than EPMC in raising the depleted catalase levels. In silico analysis revealed poor affinity of EPMC and PMCA with AChE enzyme and glutamate receptor. To conclude, PMCA and EPMC exerted cognitive enhancing property independent of direct AChE and glutamate receptor inhibition.